Cidades sobrepostas: o processo de modernização e segregação urbana de Teresina (1990-2010) - Monte, Regianny Lima (2021)
This paper is an analysis of the process of modernization and urban segregation that occurred in the city of Teresina between 1990 and 2010. This process resulted in interventions implemented with the purpose of bringing Teresina closer to other urban centers, which, due to their proportionality, were responsible for the city's inclusion in the international parameters of global cities and for this reason it began to experience problems generated by this new way of being in the urban space typical of post-modernity. New spatialities were created to meet the demands of the sector, with the opening of shopping malls and gated communities. The government acted to direct the actions, equipping the city with urban equipment that responded to the needs of a new way of living and consuming the city. This new way of being in the city is marked by individuality and the volatility of social relations. Public and civil spaces are replaced by spaces marked by the market issue, in which issues related to citizenship are replaced by a consumer relationship. However, this new way of being in the city is not accessible to everyone. A considerable part of the population does not have access to this market city and is doubly excluded, having lost spaces for community participation and being unable to participate in the capital city. However, the city is not built without conflicts; those excluded from this process or those averse to the way it was implemented will leave their impressions on all these changes that went beyond the city walls and left their reflections on the multiple forms of possible experiences within the urban space. The theoretical framework on which this research was anchored was the studies of Michel de Certeau, regarding the concepts of representation and appropriation of urban spaces, and the writings of Zygmunt Bauman and his reflections on the moment of postmodernity, which he called liquid modernity. The methodological path included a considerable amount of sources, ranging from official documents of state and municipal executives to daily newspapers.